Landform-regolith mapping in north-central Burkina Faso (West Africa): Fundamental and applied implications - (:unkn) unknown (My University, 2021)
We present an integrated landform-regolith mapping protocol/chart for West Africa developed using a case from North-central Burkina Faso. The chart is based on a high-resolution study of a typical West African landscape developed on greenstone belts of soudanian-sahelian zone. We emphasise the identification criteria of residual or detrital regoliths, whether duricrusted or not. Twenty landform-regolith units have been distinguished, which are four main types: (i) units of the older lateritic paleolandsurfaces, (ii) units that characterize Neogene pediment systems and their detrital ferruginous duricrust, (iii) erosional landform, and (iv) units that characterizing the active pediments. Fieldwork was completed by a systematic geochemical characterization of each landform-regolith association. We provide detailed geomorphological, sedimentary, petrographic and geochemical identification criteria for each West African landform-regolith association. Our work allowed constraining a high-resolution landscape evolution model for soudanian-sahelian West Africa, which is coupled with a geochemical evolution model. Landform-regolith mapping chart is transposed into a soil prospectivity chart, which is used to define mineral exploration guides such as (i) defining sampling strategies, (ii) interpreting potential geochemical anomalies, (iii) targeting lateral extensions of known bedrock mineralization, and (iv) targeting supergene mineralization. A new dispersion model of mineralized bedrock through the regolith is provided.
Keywords: African Research